2018
DOI: 10.1186/s12944-018-0671-2
|View full text |Cite
|
Sign up to set email alerts
|

Small dense low density lipoprotein-cholesterol and cholesterol ratios to predict arterial stiffness progression in normotensive subjects over a 5-year period

Abstract: BackgroundSmall dense low density lipoprotein-cholesterol (sdLDL-C), cholesterol ratios and carotid-femoral pulse wave velocity (cf-PWV) impart risk for all-cause morbidity and mortality independently of conventional cardiovascular disease (CVD) risk factors. This study was designed to identify feasible indicators for predicting arterial stiffness progression.MethodsWe followed up 816 normotensive participants without diabetes or CVD for nearly 5.0 years. Cholesterol parameters, ratios and other clinical and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 36 publications
(42 reference statements)
3
19
0
Order By: Relevance
“…TG/HDL-C was also found to be an independent determinant of arterial stiffness in adolescents and young adults [37]. Consistent with our study, subjects with high TG/HDL-C ratio also had high risk of carotid-femoral pulse wave velocity (cfPWV) progression in healthy individuals [38]. However, the result of another investigation revealed that higher cfPWV in late-life was not related to faster annual rates of change in TG/HDL-C from mid-life [36].…”
Section: Discussionsupporting
confidence: 89%
“…TG/HDL-C was also found to be an independent determinant of arterial stiffness in adolescents and young adults [37]. Consistent with our study, subjects with high TG/HDL-C ratio also had high risk of carotid-femoral pulse wave velocity (cfPWV) progression in healthy individuals [38]. However, the result of another investigation revealed that higher cfPWV in late-life was not related to faster annual rates of change in TG/HDL-C from mid-life [36].…”
Section: Discussionsupporting
confidence: 89%
“…TG/HDL-C was also found to be an independent determinant of arterial stiffness in adolescents and young adults [33]. Consistent with our study, subjects with high TG/HDL-C ratio also had a higher risk of carotidfemoral pulse wave velocity (cfPWV) progression in healthy individuals [34]. However, the result of another investigation revealed that higher cfPWV in late-life was not related to faster annual rates of change in TG/HDL-C from mid-life [32].…”
Section: Discussionsupporting
confidence: 90%
“…sdLDL is the LDL subcomponent with smaller particles (~25 nm) and higher density (~1.06). In recent years, with the advancement of lipid metabolism molecular biology, research has found that sdLDL has a strong induction effect on atherosclerosis, which may be related to the characteristics of sdLDL, including susceptibility to oxidative modification, low antioxidant content, slow clearance, and easy adherence 22 . Our study found that the level of sdLDL in the restenosis group was significantly higher than that in the patency group, indicating that the detection of sdLDL may provide a new research direction for preventing restenosis after intervention.…”
Section: Discussionmentioning
confidence: 99%